2016
DOI: 10.1016/j.ijscr.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Breast hamartoma: A report of 14 cases of an under-recognized and under-reported entity

Abstract: HighlightsMammary hamartoma is a rare benign lesion accounting for approximately 4.8% of all benign breast masses.There are several variants depending on the composition of glandular and fibroadipose elements including adenolipoma, fibroadenolipoma, and myoid hamartoma.Histologically the lesions show a haphazard admixture of benign mammary glandular tissue, fat, and fibrous strands present in varying proportions.Breast hamartomas are rarely associated with malignancies.Excision of hamartoma is considered curat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…[ 19 ] But syringomatous adenoma locates in the nipple-areolar complex, whereas LGASC occurs within breast parenchyma. Myoid hamartoma is composed of varying amounts of smooth muscle cells, mammary ducts, lobules, fibrous tissue, and adipose tissue [ 22 ] ; in contrast, LGASC does not contain smooth muscle cells. Squamous metaplasia can also detected in breast pleomorphic adenoma (PA).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] But syringomatous adenoma locates in the nipple-areolar complex, whereas LGASC occurs within breast parenchyma. Myoid hamartoma is composed of varying amounts of smooth muscle cells, mammary ducts, lobules, fibrous tissue, and adipose tissue [ 22 ] ; in contrast, LGASC does not contain smooth muscle cells. Squamous metaplasia can also detected in breast pleomorphic adenoma (PA).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its irregularity and disorganization, there is no malignant tissue interweaved within normal elements. However, in a study of 14 breast hamartomas in both males and females, one was found to have irregular borders and three showed myoid differentiation [10]. Myoid hamartomas belong to an uncommon subtype of breast hamartoma with low recurrence [11].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, breast hamartomas are indistinguishable from the more common fibroadenomas or fibrocystic breast disease. 6 However, the histological features are distinct, likely reflecting different origins. Histologically, they are characterised by densely packed enlarged lobules set within a fibrous stroma.…”
Section: Answermentioning
confidence: 99%
“…In the adult population, there have been few reported cases of recurrence or malignancy arising from breast hamartomas, and it is speculated that recurrent lesions may in fact represent multifocal disease rather than true recurrence. 6,10 Overall there is a scarcity of literature documenting breast hamartomas in the paediatric population. Given the propensity for miscategorisation, the true incidence is likely to be higher than is currently indicated in the literature.…”
Section: Answermentioning
confidence: 99%
See 1 more Smart Citation